المرأة في كتابات العلامة يوسف القرضاوي كتاب مركز المرأة في الحياة الإسلامية -أنموذجا - منصر, يسمينة; عازب الشيخ, الضاوية; بوترعة, ريمة (University of Eloued-جامعة الوادي, 2022)
"الملخص هدفت الدراسة للتعريف بموضوع ""المرأة في كتابات العلامة يوسف القرضاوي كتاب مركز المرأة في الحياة الإسلامية ـ أنموذجا ـ"" وحددت الإشكالية بالصيغة التالية: في ما تمثلت مكانة المرأة عند يوسف القرضاوي في كتابه ""مركز المرأة في الحياة الإسلامية""؟ وقد بنيت الدراسة على المنهج الوصفي التحليلي، وأبرز النتائج التي توصلت إليها الدراسة هي: ـ أن الشيخ القرضاوي فقيه الدعوة، من أبرز العلماء الذين اهتموا بقضايا المرأة، التي هي قضية قديمة قدم البشرية، وأحد أبرز الموضوعات جدلا بين العلماء والفقهاء. ـ وأن كتاب الشيخ يوسف القرضاوي ""مركز المرأة في الحياة الإسلامية"" من أكثر الكتب التي تحمل موضوع المرأة، حيث شمل المجال الاجتماعي والمجال الثقافي، وذلك بإبراز مكانتها في المجتمع الإسلامي من مساواة وعدل في الميراث والعمل وسائر الأحكام الإسلامية، لذا قامت عليه الدراسة لتوضيح موقف الإسلام من المرأة أكثر.""Abstract The study aimed to introduce the topic of ""women in the writings of the All amah Yusuf Al-Qaradawi, the Book of the center for women in Islamic life -as a model-"" the problem was identified as follows: What was the status of women represented by Sheikh Yusuf al-Qaradawi in his book ""The Center of Women in Islamic Life""? the study showed the analytical descriptive curriculum, and the study's most prominent findings are: - Sheikh al-Qaradawi Faqih al-Da'wah, one of the most prominent scholars who cared about women's issues, which is an issue as old as humanity and one of the most prominent subjects one of the most prominent topics is the debate between scholars and scholars. – Sheikh Yusuf al-Qaradawi book, ""the status of women in Islamic life"", is one of the most important books on the subject of women, encompassing the social sphere one of the most important books on the subject of women, including the social and cultural spheres, by highlighting their place in Islamic society from equality and justice inheritance, employment and other Islamic rulings, the study was based on which to clarify Islam's attitude towards women more "
مذكرة ماستر
Keywords: المرأة - كنابات- يوسف القرضاوي; Women - Kanabat - Yusuf al-Qaradawi